Numerical analysis of the stress-strain state and an optimization of the adjustable blade hydroturbine cover model - Кантор, Б. Я.; Шупиков, А. Н.; Мисюра, C. Ю. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2016)
A mathematical model of the adjustable blade hydroturbine cover was developed. Optimization with the help of the gradient method using the finite element method and cyclically symmetrical calculation scheme and numerical analysis of the stress-strain state of the cover construction were carried out. The influence of a number of the main vertical edges at a fixed number of oblique edges and small edges on the strength of the cover was investigated. It was found that the initial construction has an overstock of a strength. Optimization of a mass and a nomenclature of construction material was carried out.